2015
DOI: 10.1016/j.bbr.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Action observation and motor imagery in performance of complex movements: Evidence from EEG and kinematics analysis

Abstract: HIGHLIGHTS• The role of motor imagery (MI) and action observation (AO) methods was examined.• We analyzed brain correlates underlying learning of a complex coordination task.• Different activation patterns related to EEG spectral bands were elicited by AO and MI.• AO showed a more efficient activation of cortical resources during task execution.• AO may be more effective than MI in promoting early motor learning. ABSTRACTMotor imagery (MI) and action observation (AO) are considered effective cognitive tools fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 125 publications
2
54
0
Order By: Relevance
“…Brunner et al, (2014) reported that this improvement in motor performance may be related to activation in the inferior temporal gyrus and the thalamus, and movementrelated areas, such as premotor, supplementary, and motor cortex during action observation. Gonzalez-Rosa et al, (2015) reported action observation was associated with greater beta synchronization over bilateral parietal regions, compared with motor imagery and control groups.…”
Section: ⅳ Discussionmentioning
confidence: 82%
“…Brunner et al, (2014) reported that this improvement in motor performance may be related to activation in the inferior temporal gyrus and the thalamus, and movementrelated areas, such as premotor, supplementary, and motor cortex during action observation. Gonzalez-Rosa et al, (2015) reported action observation was associated with greater beta synchronization over bilateral parietal regions, compared with motor imagery and control groups.…”
Section: ⅳ Discussionmentioning
confidence: 82%
“…Gatti et al revealed that action observation is superior to motor imagery in the early stages of new complex motor learning, as shown by behavioral [41] and EEG data [42]. As described above, motor imagery is influenced by the environment, personal imaging ability, and mental effort.…”
Section: Application Of Motor Imagery and Action Observation To Physimentioning
confidence: 98%
“…In the early stages of new complex motor learning, action observation is superior to motor imagery as a strategy for motor learning, as revealed by behavioral [33] and EEG data ( Figure 7) [34]. Motor imagery is influenced by the environment and personal imaging ability and requires mental effort.…”
Section: Action Observation and Motor Learningmentioning
confidence: 99%
“…In other words, motor learning is Figure 7. Cortical activation patterns in the action observation (AO), motor imagery (MI), and control (C) groups [34]. Average TRPow (task-related power) changes with respect to resting baseline, within the two frequency bands showing significant group effects, were interpolated and projected onto an average brain cortical surface.…”
Section: Action Observation and Motor Learningmentioning
confidence: 99%